PERANAN TEMPAT PELELANGAN IKAN (TPI) DALAM PEMASARAN IKAN HASIL TANGKAPAN NELAYAN DI PANGKALAN PENDARATAN IKAN (PPI) KEC. TANJUNG BERINGIN KAB. SERDANG BEDAGAI PROVINSI SUMATERA UTARA - Hendrik Hendrik (Berkala Perikanan Terubuk, 2013)
This research was done at TPI of Tanjung Beringin Serdang Bedagaidistrict, aimed of this research was effect of TPI on fish market was catch byfisherman. Result of this research showed effect of TPI on fish market at TanjungBeringin village was 33,8% and market fish at Serdang Bedagai district was10,5%. Effect of this market to PAD undergo increase was 40% every year.Keywords : TPI, fish, market